Micro and Small Business Owners' Reluctance towards Halal Certification in Culinary Sector - Wahyuninsi, Wahyuninsi; Razak, Syaparuddin; Hamzah, Aksi; Husain, Hukmiah (Lembaga Sembilan Tiga Community, 2024)
This study investigates the reluctance of micro and small business actors towards halal certification in the culinary sector, as well as the influencing factors. Data were collected through questionnaires, documents, literature, and secondary data from 218 respondents in South Sulawesi. The analysis employed Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) Path Modeling approach using SmartPLS 4. Findings indicate a strong relationship between Lack of Socialization and Reluctance towards Halal Certification, weak subjective norms influencing decisions, as well as low intentions and trust levels. Low halal literacy also poses a constraint. There is a necessity for intensive socialization programs and social interactions influencing positive participation in adopting halal certification. This research provides profound insights for development strategies and policies aimed at enhancing the participation of micro and small business actors in the culinary sector, supporting the Islamic/Sharia economy, particularly in halal culinary businesses.